Open source ERP selection for small and medium enterprises by using analytic hierarchy process - Sasiporn Tasnawijitwong (2019)
© 2018 IEEE. Because of the high competition of the market, many small and medium enterprises (SMEs) seek for a suitable Enterprise Resource Planning (ERP) system to enhance the per-formance of their business, especially open source ERP systems. There are numerous of open source ERP systems today. The challenge is that most of SMEs have the limit of investment so that the appropriate open source ERP is necessary for the successful implementation. The decision making for selecting an appropriate open source ERP is important for SMEs to ensure that it is a valuable investment. This study defines important criteria that affect on decision making for open source ERP selection of SMEs and also applies these criteria with Analytic Hierarchy Process (AHP) to present the framework for selecting an appropriate open source ERP system. The results show that both qualitative and quantitative criteria influence the decision making process of open source ERP selection for SMEs. The results also show that AHP can construct the goal of open source ERP selection for SMEs and criteria affecting decision making as systematically.